Определение констант форм колебаний молекулы С2Р4; Известия вузов. Физика; Т. 59, № 7 - Фомченко А. Л. Анна Леонидовна; Белова А. С. Анастасия Сергеевна; Берёзкин К. Б. Кирилл Борисович; Зятькова А. Г. Анастасия Георгиевна (2016, 2016)
Заглавие с экрана